PENYULUHAN TENTANG SISTEM RUJUKAN PELAYANAN KESEHATAN DI MUSHOLA MUJAHIDDIN JLN.KARYA SATU, DOKAGU KELURAHAN AIR DINGIN, KECAMATAN BUKIT RAYA, KOTA PEKANBARU - Suryandartiwi, Wiwik; Tonis, Marian; Firdaus, Muhammad (Awal Bros Journal of Community Development, 2024)
The health service referral system is the organization of health services that regulates the reciprocal delegation of duties and responsibilities for health services, both vertically and horizontally. A referral system is required for patients who are participants in health insurance or social health insurance and health service providers. In this article the author describes the community service activities that have been carried out to increase public understanding of the health service referral system. Community service activities carried out in the Karya 1 dokagu area, Bukit raya District use lecture, discussion and question and answer methods. As for the results of this community activity, the community has been able to understand the health service referral system. This activity can also increase public enthusiasm or awareness in health checks and increase public awareness of healthy living